2013
DOI: 10.1073/pnas.1216382110
|View full text |Cite
|
Sign up to set email alerts
|

Chloride transport-driven alveolar fluid secretion is a major contributor to cardiogenic lung edema

Abstract: Alveolar fluid clearance driven by active epithelial Na + and secondary Cl − absorption counteracts edema formation in the intact lung. Recently, we showed that impairment of alveolar fluid clearance because of inhibition of epithelial Na + channels (ENaCs) promotes cardiogenic lung edema. Concomitantly, we observed a reversal of alveolar fluid clearance, suggesting that reversed transepithelial ion transport may promote lung edema by driving active alveolar fluid secretion. We, therefore, hypothesized that al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

5
62
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(68 citation statements)
references
References 44 publications
5
62
1
Order By: Relevance
“…However, Wolk et al (11) showed that alveolar instillation of a CFTR inhibitor decreased alveolar fluid clearance (AFC) by about 20%, suggesting the presence of transcellular Cl − movement through the CFTR. Solymosi et al (8) also report that inhibitors of the CFTR decreased AFC by 25-30%. Previously, Fang et al (12) showed that ΔF508 mice, the most common CFTR mutation, had normal levels of Na + -dependent AFC, but in contrast to wild-type mice, did not increase their AFC following instillation of β-agonists or forskolin.…”
mentioning
confidence: 96%
See 4 more Smart Citations
“…However, Wolk et al (11) showed that alveolar instillation of a CFTR inhibitor decreased alveolar fluid clearance (AFC) by about 20%, suggesting the presence of transcellular Cl − movement through the CFTR. Solymosi et al (8) also report that inhibitors of the CFTR decreased AFC by 25-30%. Previously, Fang et al (12) showed that ΔF508 mice, the most common CFTR mutation, had normal levels of Na + -dependent AFC, but in contrast to wild-type mice, did not increase their AFC following instillation of β-agonists or forskolin.…”
mentioning
confidence: 96%
“…It is possible that in mice with congestive heart failure, decreased endothelial NO synthase activity and NO levels may be an important compensatory mechanism, limiting the extent of lung edema formation. Thus, the study by Solymosi et al (8) clearly enhances our understanding of the mechanisms leading to the formation of pulmonary edema following an acute increase in left atria pressure and elucidates an important unique mechanism for the therapeutic potential of furosemide.…”
mentioning
confidence: 99%
See 3 more Smart Citations